BIOGRAFI MUHAMMAD NURDIN YUSUF SEBAGAI TOKOH PEJUANG BENGKALIS TAHUN 1920-2001 - Maulidia, Nugrah; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The struggle of the Bengkalis citizen to maintain independence and raise the merah putih flag to got difficulty from Japan, which at that time was still in power. However, when Japan lost in the Pacific war some of its leaders still in Bengkalis chose to leave Bengkalis at that time. Then the Chinese come from Malaka who came claiming to be representatives of the Allies. In the Bengkalis, the news of the proclamation was definitely received just before the middle of October 1945. Due to the limitations of the mass media at that time made the public late knowing that Indonesia was already independent. The first purpose of the study is to find out the childhood of Muhammad Nurdin Yusuf's, the second is to find out the educational history of Muhammad Nurdin Yusuf, the third is to find out struggle of Muhammad Nurdin Yusuf before and after independence Indonesian, the forth is to find out the end of the struggle of Muhammad Nurdin Yusuf. The method that used was the historical method, qualitative descriptive method, and data collection techniques in the form of interviews, literature and documentation. The results of this study can be concluded that Muhammad Nurdin Yusuf was a young man born on a Bukit Batu on 11 November 1920. He studied at the Public School in 1927 or is now it’s equivalent to a promary school then continued to study at HIS Muhammadiyah and Islamic Boarding Schools. After completing his education, Muhammad Nurdin Yusuf at the time of dutch in Bengkel Buyu actively traded in importing goods from Singapore to Bengkalis. Muhammad Nurdin Yusuf has several roles before and after Independence.Key Words: Biography, Figures, Fighters, Bengkalis.